A link between radicalisation models and extremist propaganda. Issue 1 (31st December 2022) - Msall, Kyle; Lary, Noor
ABSTRACT: This study explores the relationship between extremist propaganda and the process of radicalisation. Two theories of the radicalisation process are explored which include a linear approach and a non-linear approach. The Dabiq magazines published by ISIS were analysed qualitatively to understand the possible link between propaganda and radicalising future ISIS fighters. The findings found that the Dabiq magazines were in line with Sageman's radicalisation process which is non-linear. All of the magazine issues contained various aspects that fit into the four stages of Sageman's model which suggests that ISIS is attempting to radicalise future enlistments by using multiple methods within the Dabiq issues.